Granulomatous reactivation during the course of a leprosy infection: reaction or relapse. - Maria Angela Bianconcini Trindade; Gil Benard; Somei Ura; Cássio Cesar Ghidella; João Carlos Regazzi Avelleira; Francisco Reis Vianna; Alfredo Bolchat Marques; Ben Naafs; Raul Negrão Fleury (Public Library of Science (PLoS), 2010)
BACKGROUND: Leprosy is a chronic granulomatous infectious disease and is still endemic in many parts of the world. It causes disabilities which are the consequence of nerve damage. This damage is in most cases the result of immunological reactions. OBJECTIVES: To investigate the differences between a type 1 leprosy (reversal) reaction and relapse on using histopathology. METHODS: The histopathological changes in 167 biopsies from 66 leprosy patients were studied. The patients were selected when their sequential biopsies demonstrated either different patterns or maintained the same pattern of granulomatous reaction over more than two years during or after the treatment of leprosy. RESULTS: In 57 of the patients studied, a reactivation was seen which coincided with a decrease in the bacteriological index (BI), suggesting that this reactivation (reversal reaction or type 1 leprosy reaction) coincides with an effective capacity for bacteriological clearance. In nine patients, an increase of the bacteriologic index (IB) or persistence of solid bacilli occurred during the reactivation, indicating proliferative activity, suggestive of a relapse. The histopathological aspects of the granulomas were similar in both groups. CONCLUSION: Bacterioscopy provided the only means to differentiate a reversal reaction from a relapse in patients with granulomatous reactivation. The type 1 leprosy reaction may be considered as a part effective immune reconstitution (reversal, upgrading reaction) or as a mere hypersensitivity reaction (downgrading reaction) in a relapse.